(untitled) (Research, Society and Development, 2025)
Objectives: Analyze the impact of the exchange of experiences between undergraduates and graduates of the nursing course, highlighting its effects on the formation of future professionals, based on the performance of the Academic League of Women’s Health and Women’s Empowerment as a space for teaching, research and extension.. Methodology: This is a systematized experience report based on Holliday, through the analysis of questionnaires on professional autonomy, active listening and coordination of nursing care, discussed in 5 moments: starting point, initial questions, recovery of the experienced process, background reflection and arrival points. Results: The findings demonstrated that interaction with graduates has a positive impact on the students’ training, strengthening confidence, favoring the construction of knowledge and the development of essential skills for practice. The exchange also reinforced the importance of active listening in care and collaborative coordination in multidisciplinary teams. Conclusion: The participation of graduates in the academic environment promotes more integrated and reflective learning, broadens the understanding of the areas of nursing practice and strengthens the preparation of future professionals to face the challenges of professional practice.